Better Banking : Understanding and Addressing the Failures in Risk Management, Governance and Regulation. - Docherty, Adrian (Wiley, 2013)
Why did the financial crisis happen? Why did no one see it coming? And how did our banks lose so much of our money? What's being done to sort out the banking industry? And will it work? These are the questions that industry experts Adrian Docherty and Franck Viort cover in Better Banking: Understanding and Addressing the Failures in Risk Management, Governance and Regulation. They give a clear and thorough run-through of some of the key concepts and developments in banking, to enable the reader to understand better this vital yet perilous industry. Without excessive detail or j.